How does the use of simultaneous contrast illusion on product-background color combination nudge consumer behavior? A behavioral and event-related potential study - Peng, Minjing; Tong, Yao; Xu, Zhicheng; Jiang, Linli; Huang, Haiyang (Frontiers in Neuroscience, 2022)
Color, as one of the most critical visual factors influencing consumer decisions, has been widely used in e-commerce marketing. However, the effects of product-background saturation combination on consumers’ willingness to purchase products with different heaviness attributes (e.g., heaviness-positive products or heaviness-negative products) have not been conclusively determined. The current study demonstrated the effects of product-background saturation combination on product heaviness perception and its downstream consequences. Based on behavioral method, study 1 showed that a patch of color placed in a pale background (the saturation of the background is lower than the saturation of the color patch) was perceived as visually heavier than that in a colorful background (the saturation of the background is higher than the saturation of the color patch). Study 2 applied event-related potentials (ERPs) method to explore the underlying neural mechanisms of how the interactions between the presentation modes and the product types affect consumer decisions. Behaviorally, compared to the colorful background, the pale background would lead to a higher purchase rate for the heaviness-positive products, whereas the opposite results were found for the heaviness-negative products. Furthermore, for both the heaviness-positive and heaviness-negative products, a shorter reaction time would be observed in the pale background condition than in the colorful background condition. Neurophysiologically, the pale background would result in smaller N2 component and larger P3 component compared to the colorful background for the heaviness-positive products, while the reverse held for the heaviness-negative products. Smaller N2 component implies decreased perceptual conflicts and larger P3 component implies increased decision confidence, suggesting that e-retailers should present heaviness-positive products with pale backgrounds and heaviness-negative products with colorful backgrounds.